Pathways to Progress : Transitioning to Country-Led Service Delivery Pathways to Meet Africa's Water Supply and Sanitation Targets - African Ministers Council on Water (World Bank, Washington, DC, 2014)
The African Ministers Council on Water (AMCOW) commissioned the production of a second round of Country Status Overviews (CSOs) to better understand what underpins progress in water supply and sanitation and what its member governments can do to accelerate that progress across countries in Sub-Saharan Africa (SSA). Based on the extensive in-country diagnostics, analysis, and stakeholder consultations, the second CSO provides these insights for 32 countries in SSA, for which there are separate individual country reports. This document is the regional synthesis of the 32 country status overviews which collectively account for 95 percent of SSA's population and over 90 percent of Gross Domestic Product (GDP). The report highlights the most important trends, challenges, and proposed actions for achieving improved water supply and sanitation (WSS) services across Sub-Saharan Africa. The opportunities for progress are identified based on: understanding trends, identifying the challenge, and prioritizing action.